Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1128/aem.68.5.2576-2579.2002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Common Laboratory Disinfectants on the Infectivity of Cryptosporidium parvum Oocysts in Cell Culture

Abstract: Nine liquid disinfectants were tested for their ability to reduce infectivity of Cryptosporidium parvum oocysts in cell culture. A 4-min exposure to 6% hydrogen peroxide and a 13-min exposure to ammonium hydroxideamended windshield washer fluid reduced infectivity 1,000-fold. Other disinfectants tested (70% ethanol, 37% methanol, 6% sodium hypochlorite, 70% isopropanol, and three commercial disinfectants) did not reduce the infectivity after a 33-min exposure. The results indicate that hydrogen peroxide and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 11 publications
0
22
1
2
Order By: Relevance
“…Hydrogen peroxide is one of the few commonly used surface disinfectants with proven effectiveness against C. parvum oocysts: exposure to H 2 O 2 (6%, 4 min) reduced the oocysts infectivity in HCT-8 cells an order of magnitude (Weir et al, 2002) while a 99% loss of oocysts infectivity was also observed in MDCK cells following exposure to 3% H 2 O 2 (20 min, 20 C) and 3% H 2 O 2 was thus recommended to inactivate C. parvum oocysts in laboratory settings (Barbee et al, 1999). Gaseous H 2 O 2 has also been shown effective at sterilizing endoscopic material containing oocysts (Vassal et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen peroxide is one of the few commonly used surface disinfectants with proven effectiveness against C. parvum oocysts: exposure to H 2 O 2 (6%, 4 min) reduced the oocysts infectivity in HCT-8 cells an order of magnitude (Weir et al, 2002) while a 99% loss of oocysts infectivity was also observed in MDCK cells following exposure to 3% H 2 O 2 (20 min, 20 C) and 3% H 2 O 2 was thus recommended to inactivate C. parvum oocysts in laboratory settings (Barbee et al, 1999). Gaseous H 2 O 2 has also been shown effective at sterilizing endoscopic material containing oocysts (Vassal et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the resistance of these fish microsporidia to chlorine, other disinfectants that do not injure fish embryos within eggs should be evaluated for killing spores. Hydrogen peroxide has been used to kill resistant stages of other protozoa, such as Cryptosporidium species (Weir et al 2002). Dilute formalin (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Ozone, another popular water disinfectant, has proven to be much more efficient in killing oocysts, although its instability makes it difficult to maintain high levels in water for periods of time sufficient for treatment under practical conditions (20). The oocysts are also unaffected by commonly used laboratory disinfectants such as 6% sodium hypochlorite, 70% ethanol, and a variety of commercial preparations used domestically or in animal husbandry (28), although exposure to 10% Formol, aqueous or gaseous ammonia, or hydrogen peroxide has been reported to greatly reduce or eliminate oocyst infectivity (1,9,23). Low concentrations of ammonia (0.007 M) significantly decrease the viability of oocysts after 24 h of exposure, as determined with in vitro assays (19), and a 4-min exposure to 6% hydrogen peroxide or a 13-min exposure to ammonium hydroxide-amended windshield washer fluid reduces infectivity of C. parvum oocysts in cell culture 1,000-fold (28).…”
mentioning
confidence: 99%